2013
DOI: 10.1007/s12020-013-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating chemerin decreases in response to a combined strength and endurance training

Abstract: Chemerin is an adipokine that may mediate the link between obesity, inflammation, insulin resistance, type 2 diabetes mellitus, and cardiovascular disease. In this study, we examined the association between chemerin and various cardiometabolic risk factors in cross-sectional setting and tested the hypothesis that a 6-month combined exercise program decreases serum chemerin in overweight or obese, non-diabetic individuals. Serum chemerin concentration was measured in a cross-sectional analysis including 98 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…Additionally, two recent studies observed associations between changes in chemerin and improvements in insulin sensitivity following chronic exercise interventions. Stefanov et al (2014) found decreases in serum chemerin following a 6-month endurance and resistance training regimen to be associated with concomitant decreases in HOMA-IR. Likewise, Kim et al (2013) observed a correlation between decreases in serum chemerin and improvements in the insulin sensitivity index following a 12-week lifestyle modification program which also included both aerobic and resistance exercise.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, two recent studies observed associations between changes in chemerin and improvements in insulin sensitivity following chronic exercise interventions. Stefanov et al (2014) found decreases in serum chemerin following a 6-month endurance and resistance training regimen to be associated with concomitant decreases in HOMA-IR. Likewise, Kim et al (2013) observed a correlation between decreases in serum chemerin and improvements in the insulin sensitivity index following a 12-week lifestyle modification program which also included both aerobic and resistance exercise.…”
Section: Discussionmentioning
confidence: 80%
“…The levels of chemerin, an adipokine identified fairly recently, were correlated with body mass index (BMI) and components of the metabolic syndrome in normal and overweight subjects [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]. It has also been shown that the levels of chemerin in patients with metabolic syndrome are significantly correlated with BG, high density lipoprotein-cholesterol (HDL-C), CHOL, TG, CRP, fasting insulin and the homeostatic model assessment (HOMA) index [18,[20][21][22], whereas a negative correlation exists with the glomerular filtration rate (GFR) [23]. Studies also indicate that serum chemerin levels are significantly elevated in patients on chronic hemodialysis and are correlated with renal function [7].…”
Section: Discussionmentioning
confidence: 97%
“…High blood pressure could be a potential link given that it contributes both to metabolic syndrome and is a major risk factor for cardiovascular disease. Circulating chemerin concentration positively correlates with both systolic and diastolic blood pressure in a range of patient populations, particularly those with obesity, metabolic syndrome, type 2 diabetes mellitus, and type 2 diabetes mellitus with hypertension, and these patient groups are at higher risk of developing cardiovascular disease. Our data show, for the first time, that chemerin causes concentration‐dependent contraction of human blood vessels and has a direct effect on blood pressure in rats by binding to CMKLR1 on the smooth muscle layer.…”
Section: Discussionmentioning
confidence: 99%